Re-description of the genus Heterobiantes and its type species H. geniculatus (Opiliones: Laniatores: Epedanidae) with additional genital and external morphology data - Tan, Desmond Kai Teck; Fong, Jonathan J.; Zhang, Chao (Zootaxa, 2023)
The genus Heterobiantes Roewer, 1912 and its type species Epedanus geniculatus Pocock, 1903 are redescribed based on the type specimen currently housed within the British Museum of Natural History (BMNH), London, along with new specimens captured in Hong Kong, providing updated morphological data and male genital description. Closer inspections reveal how the species is different from other similar genera within Epedaninae and rationalizes its placement as a monotypic genus within the sub-family. Genetic data are also included.